2015
DOI: 10.5433/1679-0359.2015v36n3p1531
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic stability, chemical composition and ruminal degradability of sugarcane silage with glycerin from biodiesel

Abstract: The experiment was performed with the objective of studying the ensiled sugarcane silage with 0, 5, 10, 15 and 20% of glycerin in experimental PVC silos. The aerobic stability was assessed by measuring the pH and the temperature of the silage at 0, 24, 48, 72, 96 and 120h. The chemical composition, the levels of non-fiber carbohydrates (NFC) and the total digestible nutrients (TDN) were evaluated. The in vitro digestibility of dry matter (IVDDM) and the in vitro digestibility of the cell wall (IVDCW) in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
1
8
1
1
Order By: Relevance
“…Similar results were reported by Gomes et al (2015), who observed a reduction by 37.56% in the CP concentration of sugarcane silages added with 150 g kg −1 of fresh matter glycerin compared with control silages. This is often reported because additives used to promote fermentation are rich in energy and present low protein content.…”
Section: Discussionsupporting
confidence: 78%
“…Similar results were reported by Gomes et al (2015), who observed a reduction by 37.56% in the CP concentration of sugarcane silages added with 150 g kg −1 of fresh matter glycerin compared with control silages. This is often reported because additives used to promote fermentation are rich in energy and present low protein content.…”
Section: Discussionsupporting
confidence: 78%
“…The castor bean meal was purchased from agribusiness in the metropolitan region of Salvador-BA, which was previously detoxified using lime solution Ca(OH) 2 . Each kg was diluted in 10 liters of water and applied in the amount of 60 grams of lime per kg of meal at natural matter basis, as recommended by Oliveira et al (2015). After mixing the meal with the lime solution, the material stayed still for twelve hours (overnight).…”
Section: Methodsmentioning
confidence: 99%
“…Daniel et al (2013) found that sugarcane silages can contain up to 22% volatile compounds, with ethanol representing most of it. From de ensiling process, there is roughage rich in neutral detergent insoluble fiber (77%) and with a low crude protein content (4%) (Gomes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations can be minimized with additives aimed at improving the fermentation profile and minimizing dry matter losses through effluents and gases. Among the potential additives, crude glycerin has a high dry matter content (90%) and a high glycerol content (80%), which can be a source of energy for fermentative bacteria, and it is also highly available due to the recent increase in biodiesel production that has caused the prices of this industrial by-product to decrease, making its use attractive (DIAS et al, 2014;GOMES et al, 2015;RIGUEIRA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%